Abdominal peripheral nerve block as the only anesthetic technique for totally extraperitoneal endoscopic inguinal hernia repair: Two case reports. Issue 24 (June 2018) - Kwon, Woojin; Bang, Seunguk; Soh, Hyojung; Jeong, Won Jun; Lee, Sang Chul; Choi, Byung Jo
Abstract: Rationale: Laparoscopic totally extraperitoneal (TEP) inguinal hernia repair is a rapidly evolving, minimally invasive treatment modality for inguinal hernia. Compared with open hernia repair, this method requires a smaller incision, has cosmetic advantages, and facilitates rapid recovery and early return to daily activities because of less postoperative pain. Because general anesthesia is essential for TEP hernia repair, it cannot be performed on patients who have an increased risk of developing complications when placed under general anesthesia. Patient concerns: We report 2 cases of single-port laparoscopic TEP (SP TEP) that were performed using only an abdominal peripheral nerve block (PNB) at our institute. General anesthesia and neuraxial block were dangerous for both patients owing to severe heart failure and severe chronic obstructive pulmonary disease (COPD). Diagnoses: They were diagnosed with an inguinal hernia requiring surgery. Interventions: Hence, the anesthesiologist and surgeon decided to attempt a PNB to avoid complications from general anesthesia and allow faster recovery. An ipsilateral transversus abdominis plane block as well as a rectus sheath block and inguinal canal block were administered via ultrasound guidance. Outcomes: The patients did not report any pain, and no rescue drug was administrated. The operation times were 65 and 62minutes in patients 1 and 2, respectively. No intraoperative complications were noted. Patient 1 was discharged the day after the surgery, whereas patient 2 was discharged on the same day as the surgery. Lessons: TEP hernia repair using abdominal PNB anesthesia seemed to be a safe and feasible technique without causing any additional complications. However, the use of abdominal PNB anesthesia alone for TEP hernia repair as an alternative to general anesthesia requires further investigation using a larger cohort.